2017
DOI: 10.1016/j.ophtha.2017.04.021
|View full text |Cite
|
Sign up to set email alerts
|

24-2 Visual Fields Miss Central Defects Shown on 10-2 Tests in Glaucoma Suspects, Ocular Hypertensives, and Early Glaucoma

Abstract: Purpose To investigate the prevalence of visual field defects in glaucomatous eyes, glaucoma suspects, and ocular hypertensives with 24-2 and 10-2 visual fields. Design Prospective, cross-sectional study. Participants Patients with or suspected glaucoma. Testing 24-2 and 10-2 visual fields. Patients were classified into 3 groups based upon the presence of glaucomatous optic neuropathy (GON) and 24-2 visual field abnormalities: early glaucoma (GON and abnormal visual field, mean deviation >−6 dB), glaucom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
121
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 167 publications
(129 citation statements)
references
References 28 publications
5
121
0
3
Order By: Relevance
“…In recent years, this misconception has been challenged by investigators who used different methods to reach very similar conclusions. 7,9,10,[13][14][15]30 Another important reason is the more recent implementation of SD-OCT for glaucoma diagnosis and monitoring. High-resolution imaging of the macula has allowed the visualization of the RGCP layer, where glaucomatous damage occurs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, this misconception has been challenged by investigators who used different methods to reach very similar conclusions. 7,9,10,[13][14][15]30 Another important reason is the more recent implementation of SD-OCT for glaucoma diagnosis and monitoring. High-resolution imaging of the macula has allowed the visualization of the RGCP layer, where glaucomatous damage occurs.…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence that 24-2 SAP results can miss damage within the central 10°of the visual field that would otherwise be detected if one used a denser grid (2 × 2°), such as that tested with 10-2 SAP. [7][8][9][10][11][12][13][14][15] Furthermore, studies using spectral-domain optical coherence tomography (SD-OCT) have shown that macular damage in early glaucoma is much more common than previously thought and is often present in eyes with 24-2 mean deviation (MD) better (ie, closer to 0) than −6 dB. [16][17][18][19][20] Because of their importance in clinical and research settings, and given their substantial association with measures of vision-related quality of life, 21,22 24-2 (or 30-2) SAP metrics have traditionally been used to stage glaucoma severity.…”
mentioning
confidence: 99%
“…However, in a recent study in the US 22 in patients with suspected glaucoma, 79 of the 200 eyes (39.5%) classified as normal on the 24-2 test were classified as abnormal on 10-2 visual fields. In ocular hypertensive eyes, 28 of the 79 eyes (35.4%) classified as normal on the 24-2 test were classified as abnormal on the 10-2 test.…”
Section: A Further Interesting Development Comes From the Primary Tubmentioning
confidence: 92%
“…76 It has also been suggested that the 10-2 visual field may be a more appropriate outcome measure as the 24-2 field can underestimate the degree of damage at the macular region involved in glaucomatous optic neuropathy. 77 The 10-2 visual field has also been shown to correlate with quality of life outcome measures 78 and may reduce the time required to detect glaucomatous progression. 79 Wu et al also indicates that lengthy and large trials are not essential, suggesting that the sample size required to assess the effect of any neuroprotective intervention depends on the baseline rate of progression, study duration, and quantification and outcome parameter.…”
Section: Optimising Clinical Trial Endpointsmentioning
confidence: 99%